THE GROWTH OF WHITE SHRIMP (Litopenaeus vannamei) GIVEN PROBIOTIC CULTIVATED IN VARIOUS FERMENTED CARBON SOURCES - Citria, Ika; Abidin, Zaenal; Astriana, Baiq Hilda (Jurnal Perikanan Unram, 2018)
The goals of this study were to know the effect of utilization of various carbon sources fermented on growth of probiotic bacteria and to know the effect of the probiotic application on shrimp (Litopenaeus vannamei) growth. The experiment was conducted at Balai Pengembangan Budidaya Perikanan Pantai (BPBPP), West Nusa Tenggara. The probiotic bacteria werecultivated by using three different fermented carbon sources, i.e., fermented tapioca, fine bran, and corn meal. The bacteria then were tested to the postlarva 20 of shrimp. The result showed that all of the carbon sources increased the number of colony of bacteria on 7th and 30th days. Tapioca as a carbon source resulted in the highest number of colony by 3.69x1011 CFU/ml compared to fine bran and corn meal. The utilization of probiotic bacteria resulted from the multiplication showed that probiotic using tapioca as carbon source resulted in the highest growth rate compared with those of other carbon sources.